THE ANTIMICROBIAL PROPERTIES OF MARINEDERIVED NANOPARTICLES - KHAMRAEV , ABROR; UGLI , ERGASHEV BUNYOD SHOKIR; ALII , HASAN MUHAMMED; EKAMBARAM, YASVANTHRA; PRADHAN , MR. SACHIN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Bioactive compounds have been discovered in a wide variety of marine organisms, including fish, algae, plankton, fungi, bacteria, marine mammals, and invertebrates. These active chemicals derived from marine sources have been employed extensively because of their various biological properties. Whole extracts or pure chemicals are employed to create nanoparticles because marine-derived materials are easily accessible, inexpensive to generate, nontoxic, and have low cytotoxicity against eukaryotic cells. Both infectious diseases caused by bacteria, fungi, and viruses as well as non-infectious conditions like cancer, diabetes, inflammatory response, and tumors have been treated with these marine-derived nanomaterials. They have also been applied to encourage the healing of wounds. Additionally, several marine polymers, such alginate and chitosan, are employed as drug delivery nanocarriers. Additionally, after being encapsulated onto polymeric nanocarriers, a range of pure bioactive chemicals have been used to treat infectious and non-infectious disorders. This paper aims to give a comprehensive overview of the creation of nanoparticles and their biological applications using their pure components or complete extracts that have been extracted from marine resources.